The development of assessment instrument for postpartum patients with severe preeclampsia-eclampsia based on need for help and self-care models - Endah Suprihatin; Sri Hardi Wuryaningsih (Universitas Airlangga, 2022)
Introduction: One of the causes of the high mortality rate of patients with severe preeclampsia-eclampsia in the postpartum period is the inaccurate assessment of the patient's need for help and independence in self-care. This study aimed to develop specific assessment instruments for postpartum patients based on Wiedenbach’s need for help and Orem’s self-care models. Methods: This study used a research and development (R&D) approach. The samples were 30 midwives and 100 documents of postpartum patients with preeclampsia from Airlangga University Hospital, Surabaya, and 30 midwives from Haji Hospital Surabaya. Data were collected through document tracking and interviews. Data were analyzed with R&D methods. Results: The results showed that the mean rank value of the new assessment instrument was higher (29.72) than the old assessment instrument (19.93). A significant difference was found between the new assessment instrument and the old assessment instrument (Wilcoxon test value -5.379 with p < 0.001). The new instrument had functionality, efficiency, and usability for assessment of the need for help and self-care of postpartum patients with severe preeclampsia and eclampsia. Conclusions: Postpartum patients with severe preeclampsia-eclampsia should be assessed by the specific assessment instruments based on Wiedenbach’s need for help and Orem’s self-care models.